PROGRAM KEWIRAUSAHAAN DI ERA PANDEMI - Novita Wahyu Setyawati; Dewi Sri Woelandari PG; Agus Dharmanto (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Community service activities that will be carried out are in the form of counseling the community through mentoring activities on economic resilience in the COVID-19 pandemic situation. The target audience in this Community Service activity are local residents. The implementation of community service is carried out by counseling first and then providing assistance to the practice of the counseling. Availability of experts from Bhayangkara University Lecturers, Bekasi, and assistant staff from students, participants (community) so that this Community Service activity is carried out. The benefits obtained from this Community Service activity include being able to help the community in creative thinking and innovation in maintaining the economy during the COVID-19 pandemic based on entrepreneurship to be able to support and maintain current conditions